Treatment Integrity and Social Validity of the FRIENDS for Life Programme in a Northeastern Canadian School System. Issue 2 (16th June 2020) - Doyle, Susan; Francis, Sarah E.; Joy, Rhonda
Abstract: The FRIENDS for Life (FFL) programme, a school-based anxiety prevention programme, targets anxiety reduction and resiliency development in elementary school-aged children (Barrett, Sonderegger & Xenos, 2003 ). In the context of equivocal effectiveness findings regarding FFL in Canadian schools, the present study assessed pre–post changes in anxiety, self-esteem, and prosocial behaviour in a school system in Northeastern Canada. To yield further insight to the potential sources of equivocal FFL effectiveness findings, we also evaluated FFL treatment integrity (TI) and social validity (SV). Few studies have assessed FFL TI at the level of identifying which programme sessions, or within-session content, have or have not been adhered to (Higgins & O'Sullivan S, 2015 ). Similarly, few studies have provided detailed programme SV data or perceived programme benefits by children and parents. TI and SV can provide programme data beyond anxiety reduction, which is key in prevention programming research, as pre–post changes are challenging to detect in 'healthy' samples (Durlak & Wells, 1997 ). Treatment outcome, TI, and SV data were collected from classrooms across 10 elementary schools administering FFL. The sample included 210 child and 108 parent participants; post-testing occurred 1 week following FFL programme completion. Findings indicated significant decreases from pre- to post-test in child-reported anxiety and self-esteem but no changes in prosocial behaviours. Findings suggest that low TI ratings may have impacted anxiety, self-esteem, and prosocial behaviour results, and that child-reported SV may be more related to programme outcomes than parent-reported SV. Implications for FFL programme developers and future FFL evaluation studies are discussed.